Experimental games scaled out to 250,000 households to improve ground and surface water governance in India - CGIAR Research Program on Policies, Institutions, and Markets (2019)
In India, rapid decline in groundwater levels is a serious challenge in many areas. With support from PIM and WLE, IFPRI partnered with the Foundation for Ecological Security, a major Indian NGO, to develop and test the use of experimental games to strengthen groundwater governance at the community level. ICRISAT developed similar tools for managing surface water. These tools are being scaled out to over 3,700 communities involving some 250,000 households in at least six Indian states.